A natureza jurídica do plano econômico de desenvolvimento na ordem constitucional brasileira - Breno Dias Blau (2013)
This academic research focuses on the legal nature of the Brazilian Economic Plan. At first we attempted to define the object of study through analytical method, through which were defined the essential features of planning. Then, after a brief historical foreshortening on the Brazilian experience in the field of economic planning, it was found that in none of the three national experiences addressed the state reconciled the pursuit of economic growth with the reduction of social inequalities. It was found also that the discrepancy between economic activity of the state and the duty which is prescribed to it by the Constitution, do not have as source the lack of coercivity of the rules of the Plan, as submitted by part of legal doctrine. The source of that discrepancy is the conceptual narrowness inherent to the legal theory that served to support the interpretation and application of law in those periods. At the end, after briefly discuss the constraints imposed by the theory of right that has informed the theoretical discussions about the economic plan, we suggest the adoption of a broader thesis: one thesis capable to understand a normative standard in conjunction with its finalistic content. The legal theory suggested was proposed by Ronald Dworkin: law as integrity. It is argued that this approach is best suited to the recognition of legal status to normative patterns present in the Economic Plan - patterns impregnated by policy reasons and based on principles linked with human rights promotion. We conclude, in agreement with this thesis, the Economic Plan is an expression of the right - but not because it takes the form of law, but because it is based on principles of political morality which are legally binding on the State.